MEDIA CONVERGENCE AS A HALLMARK OF MODERN MARKETING COMMUNICATION - Ewa Badzińska (Polityki Europejskie, Finanse i Marketing)
New information and communication techniques constantly change people's lives and the way in which consumers acquire new knowledge, conduct commercial transactions, the way they work and how they spend their free time. Virtual reality has become a real place of their residence. The aim of this study is to characterize new media from the perspective of convergence, where old and new media complement each other and interact in order to most effectively reach recipients with their message. The special role of the development of "cultural convergence" and "culture of participation" in the creation of social networking and marketing communications has been emphasized. This paper is of research and analytical character.